2017
DOI: 10.1007/s00128-017-2033-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quaternary Ammonium Salts with Fluorine Atoms on Selected Weed Species

Abstract: This study investigated the effects of four structurally different quaternary ammonium salts (QASs), i.e., tetrabutylammonium tetrafluoroborate [TBA][BF4], tetrahexylammonium tetrafluoroborate [THA][BF4], tetrabutylammonium hexafluorophosphate [TBA][PF6], and tetrahexylammonium hexafluorophosphate [THA][PF6], on the growth and development of three weed species: gallant soldier (Galinsoga parviflora Cav.), white goosefoot (Chenopodium album L.) and common sorrel (Rumex acetosa L.). The examined compounds were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…; other studies reported the occurrence of toxic effects on the physiology of Chlorella pyrenoidosa, C. vulgaris and Scenedesmus quadricauda (Jing et al, 2012;Liang et al, 2013;Zhang et al, 2015;Zhu et al, 2010). Negative effects of QACs on chlorophylls and carotenoids have been reported also in higher plants, with damages being doseand time-dependent (Biczak et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…; other studies reported the occurrence of toxic effects on the physiology of Chlorella pyrenoidosa, C. vulgaris and Scenedesmus quadricauda (Jing et al, 2012;Liang et al, 2013;Zhang et al, 2015;Zhu et al, 2010). Negative effects of QACs on chlorophylls and carotenoids have been reported also in higher plants, with damages being doseand time-dependent (Biczak et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Pawlowska et al [26] investigated the inhibitory effect of ILs containing asymmetric cations (ammonium) on the photosynthetic pigment production of common radish and spring barley. Biczak et al [107] studied the impact of the anion of quaternary ammonium salts with a fluorine atom on selected weeds species. Greater reduction of chlorophyll pigments occurred due to [PF 6 ] containing quaternary ammonium salt.…”
Section: Effect Of Ionic Liquids On the Chlorophyll Contentsmentioning
confidence: 99%
“…Biczak et al. 107 studied the impact of the anion of quaternary ammonium salts with a fluorine atom on selected weeds species. Greater reduction of chlorophyll pigments occurred due to [PF 6 ] containing quaternary ammonium salt.…”
Section: Effect Of Ionic Liquids On the Morphology Of Plantsmentioning
confidence: 99%
“…It is water-soluble electrolyte with high-degree of interand intra-molecular hydrogen bonding. It has been successfully used extensively in electrochemistry, not only as a support electrolyte in aqueous and non-aqueous solvent systems, but also in many different electrochemical methods of analytical and industrial interest [13][14][15].…”
Section: The Quaternary Tetrabutylammonium Tetrafluoroborate ([Tba][bf4]mentioning
confidence: 99%